2023
DOI: 10.1021/jacs.3c00713
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry and Biology of Collagen Hybridization

Abstract: Collagen provides mechanical and biological support for virtually all human tissues in the extracellular matrix (ECM). Its defining molecular structure, the triple-helix, could be damaged and denatured in disease and injuries. To probe collagen damage, the concept of collagen hybridization has been proposed, revised, and validated through a series of investigations reported as early as 1973: a collagen-mimicking peptide strand may form a hybrid triple-helix with the denatured chains of natural collagen but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 156 publications
1
9
0
Order By: Relevance
“…The Brillouin shift, indicative of the elastic modulus of the cornea, exhibits a pronounced peak at approximately 60 -63°C, signifying a critical change in corneal stiffness. This observation aligns with the anticipated thermal-induced denaturation of collagen, characterized by a transition from the native triple helical structure to a disordered gelatin-like arrangement, resulting in a weakened stromal network [41]. Concurrently, the full width at half maximum (FWHM) values, which reflect the viscoelastic damping properties and acoustic phonon life cycle within the tissue, progressively increase and culminate in a marked surge at this temperature range.…”
Section: Phase Transitions: Raw Spectral Indicatorssupporting
confidence: 80%
“…The Brillouin shift, indicative of the elastic modulus of the cornea, exhibits a pronounced peak at approximately 60 -63°C, signifying a critical change in corneal stiffness. This observation aligns with the anticipated thermal-induced denaturation of collagen, characterized by a transition from the native triple helical structure to a disordered gelatin-like arrangement, resulting in a weakened stromal network [41]. Concurrently, the full width at half maximum (FWHM) values, which reflect the viscoelastic damping properties and acoustic phonon life cycle within the tissue, progressively increase and culminate in a marked surge at this temperature range.…”
Section: Phase Transitions: Raw Spectral Indicatorssupporting
confidence: 80%
“…Sodium is generally acknowledged for its high reactivity and flammability. [5][6] When it comes into contact with water, it produces sodium hydroxide, which disrupts the protective oxide layer on sodium and accelerates oxidation, leading to a vigorous and uncontrollable reaction. The heat 20 released by the reaction converts water from the liquid phase to the gas phase, leading to severe expansion of the system and increasing its danger.…”
Section: Sodium Burningmentioning
confidence: 99%
“…The utilization of biomimetic soft materials, inspired by biological tissues and structures, has gained significant traction in various fields, leading to the development of novel materials with comparable physical properties [1][2][3][4][5]. Research has demonstrated the existence of collagen supramolecular assemblies in skin, ligaments, and other areas, composed of interconnected linear helical protein molecules forming elastic fiber networks [6,7]. When subjected to unidirectional stretching, these micro helical structures initially diverge and align with the loading direction, resulting in an approximate spring lattice network.…”
Section: Introductionmentioning
confidence: 99%